2023
DOI: 10.31080/asms.2023.07.1495
|View full text |Cite
|
Sign up to set email alerts
|

Community’s Mask Wearing Practice and its associated Undesirable Side Effects Among Iraqi Population Group in COVID-19 Era

Abstract: Assessing the principles, knowledge, attitude, and compliance of the Iraqi population group with regard to mask use; raising awareness and accountability, counseling them on the value of wearing masks, and researching the most common negative effects of mask use among them.Materials and Methods: 1205 responses to an online survey with a cross-sectional design were gathered from healthy Iraqi backgrounds, ranging in age from 11 to 65 and with varying levels of education. The survey was divided into 5 components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(106 reference statements)
0
0
0
Order By: Relevance
“…Anwar and Al-Bayati, [26] in Samara discovered that 30% of patients were positive for HCMV IgM and 70% were positive for Ali and Al-Ahmer, [27] reported significant levels of CMV IgG positivity 72.3% and HCMV IgM positivity 72.2% in pregnant women who underwent abortions were. In Baquba the finding of Hussein et al [28] showed that 36% HCMV positivity in pregnant women with spontaneous abortion. However, the presence of IgM indicates that the women had recently been infected or re-infected with HCMV, and that the IgM was produced shortly after infection and dissipated within a short period of time.…”
Section: Immunological Detection Of Cytomegalovirus By Elisamentioning
confidence: 96%
“…Anwar and Al-Bayati, [26] in Samara discovered that 30% of patients were positive for HCMV IgM and 70% were positive for Ali and Al-Ahmer, [27] reported significant levels of CMV IgG positivity 72.3% and HCMV IgM positivity 72.2% in pregnant women who underwent abortions were. In Baquba the finding of Hussein et al [28] showed that 36% HCMV positivity in pregnant women with spontaneous abortion. However, the presence of IgM indicates that the women had recently been infected or re-infected with HCMV, and that the IgM was produced shortly after infection and dissipated within a short period of time.…”
Section: Immunological Detection Of Cytomegalovirus By Elisamentioning
confidence: 96%